Anesthetic Management of a 4 Days Old Sub-Acute Puerperal Uterine Inversion with General Anesthesia - Wahi, Ajay; Bansal, Sapna; Gupta, Ritu; S.S. Bajwa (Academia Anesthesiologica International, 2020)
Uterus inversion is one of the rare and potentially life-threatening uncommon complications of the puerperium and subacute type is even rarer. A case is hereby reported of a 24-year-old primipara who was referred to our institute from a peripheral hospital with 4 days old uterine inversion. Inversion of the uterus was corrected under general anesthesia with halothane and maintained in anatomical position with the help of uterotonic drugs.